Virulência, resistência aos antimicrobianos e distribuição espacial e sazonal de Campylobacter coli isoladas de carcaças de frangos no Brasil - Buiatte, Ana Beatriz Garcez (2021)
Campylobacter is one of the four most isolated foodborne diarrheal disease pathogens in the world, and C. coli is the second most closely related species to human campylobacteriosis. The pathogen is often isolated from chicken carcasses. Brazil is the largest exporter of chicken meat in the world, which places the country in a prominent position, and makes the characterization of C. coli in the country's slaughterhouses extremely important for the establishment of control measures. The dissertation was divided into two chapters, and the first chapter brings a bibliographical research to contextualize the reader about the subject, which will be addressed in the later chapter. The second chapter presents an epidemiological study of 83 strains of C. coli isolated from chicken carcasses slaughtered in establishments under Federal Inspection in three Brazilian states.The strains were isolated by the Ministry of Agriculture, Livestock and Supply, through the ISO 10272:2017 methodology, and later, they were discriminated by species through mass spectrometry (MALDI-TOF). At the Molecular Epidemiology Laboratory of the Federal University of Uberlândia, the isolates were subjected to conventional PCR for 14 genes related to virulence, which were divided into five categories: biofilm formation (flaA, luxS), secretion system (cdtABC, hcp), invasion and colonization (cadF, ciaB, pldA), stress adaptation (dnaJ, htrA, cbrA), and Guillain-Barré syndrome induction (neuA, cstII). With the results, through the virulence profiles, indices of variability, virulence and multivirulence were determined. The strains were also submitted to the minimum inhibitory concentration test, to assess the phenotypic sensitivity to ciprofloxacin and erythromycin. In the end, a dendrogram of the isolates was generated from the spectra generated in the MALDI-TOF, in order to assess the distribution of the strains. C. coli isolates showed high virulence and specialization in invasion and colonization. The isolates showed 89.2% (76/83) resistance to ciprofloxacin and 55.4% (46/83) to erythromycin. Widespread genetic diversity was observed in state I, and states II and III showed local specificity. Our results suggest high virulence potential, resistance to the recommended antimicrobials in the treatment of campylobacteriosis, evidence of cross contamination and maintenance of virulent genotypes, emphasizing the need to adopt control measures in Brazilian slaughterhouses.